Corruption in public administration: An analysis of international scientific publications (Research, Society and Development, 2021)
The study seeks to identify the panorama of public administration corruption publications in the international literature over the past two decades. For data analysis we used Scopus database and a mixture of bibliometrics, content analysis, network analysis and word cloud techniques. Therefore, this research is delineated as descriptive, bibliometric and quantitative analysis. A total of 311 articles were found in the US with a more significant representation in international production with 21.1% of articles, followed by Australia (8.6%) and the United Kingdom (6.1%). Already Brazil appears in 24th place with only 4 (1.2%) publications. The results showed that the International Journal of Public Administration and Public Administration and Development, with 15 articles each, followed by the Public Administration Review, 14, and the Mediterranean Journal of Social Sciences, 10, were the top journals in number. publications on corruption in the public administration. Also, only five clusters with five or more co-authoring research links were identified, indicating that there is a low rate of cooperative research development. Moreover, the data seem to show that the world literature on the subject is relatively consolidated, unlike the national literature, which still needs further advances.